2017
DOI: 10.1177/0021998317714855
|View full text |Cite
|
Sign up to set email alerts
|

Tension–tension fatigue performance and stiffness degradation of nanosilica-modified glass fiber-reinforced composites

Abstract: The aim of this study is to investigate the influence of nanosilica on glass-reinforced epoxy composites under static mechanical and tension–tension fatigue loading. The glass-reinforced epoxy composites were manufactured with three different concentrations of nanosilica (6, 7, and 8 wt%). Static mechanical tests include tensile, flexure and short-beam strength. 6 wt% nanosilica composites showed the greatest enhancement in tensile strength, percentage elongation, and inter-laminar shear strength compared to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 20 publications
0
15
1
Order By: Relevance
“…The composite containing 6 wt% of nanosilica showed the highest increase in tensile strength (22%) and elongation and interlaminar shear strength (ILSS) (26%). The composite containing 7 wt% of nanosilica had the highest elastic modulus and flexural strength [ 40 ]. Ravi et al investigated the effect of reinforcing the composite with PMMA and silicon carbide (SiC) beads.…”
Section: Hybrid Compositesmentioning
confidence: 99%
“…The composite containing 6 wt% of nanosilica showed the highest increase in tensile strength (22%) and elongation and interlaminar shear strength (ILSS) (26%). The composite containing 7 wt% of nanosilica had the highest elastic modulus and flexural strength [ 40 ]. Ravi et al investigated the effect of reinforcing the composite with PMMA and silicon carbide (SiC) beads.…”
Section: Hybrid Compositesmentioning
confidence: 99%
“…In another study Tate et al investigated a typical system for rotor blades for wind energy generators [ 67 ]: a ±45° multiaxial glass fiber fabric was impregnated by an amine-cured DGEBA using a VARTM process. A modification with 6 wt % silica nanoparticles increased both tensile and flexural modulus, tensile and flexural strength as well as ILSS.…”
Section: Improving Epoxy Resin Applications With Silica Nanoparticmentioning
confidence: 99%
“… Stress versus number of cycles until failure (S–N) curves for unmodified and 6 wt % SiO 2 -containing epoxy GFRC [ 67 ]. …”
Section: Figurementioning
confidence: 99%
“…Tate et al. 3 investigated the influence of 6 wt%, 7 wt%, and 8 wt% nanosilica on glass fiber-reinforced epoxy composites in static mechanical and fatigue loading. It was observed that 6 wt% loading has a greater effect on tensile strength, percentage elongation, and interlaminar shear strength (ILSS).…”
Section: Introductionmentioning
confidence: 99%
“…The effect of nanosilica on tensile properties of epoxy nanocomposites is studied by Jumahat et al 2 and it was found that at 25 wt% loading level of nanosilica, improvement in modulus and strength is about 38% and 24%. Tate et al 3 investigated the influence of 6 wt%, 7 wt%, and 8 wt% nanosilica on glass fiber-reinforced epoxy composites in static mechanical and fatigue loading. It was observed that 6 wt% loading has a greater effect on tensile strength, percentage elongation, and interlaminar shear strength (ILSS).…”
Section: Introductionmentioning
confidence: 99%